PENGARUH INVESTMENT OPPORTUNITY SET DAN STRUKTUR MODAL TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Wandira, Ayu; Sosrowidigdo, Suryanto (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2024)
Financial ratio analysis is a tool for analyzing business achievements that explains various financial relationships and indicators. Data processing methods are methods used in conducting research to obtain a conclusion from the research conducted. Judging from the framework of thought and explanation that has been presented previously, the technique used in conducting this research is quantitative analysis. In this research, the analysis used to determine the effect of Investment Opportunity Set and Capital Structure on Earnings Quality uses descriptive statistical tests, classical assumption tests, t tests, f tests, and coefficient of determination tests. If the significance value (sig) of the variable is lower than the specified significance level, namely 0.000 (less than 0.05), then it can be concluded that the Investment Opportunity Set partially has a significant influence on Earnings Quality. If the significance value (sig) of the variable is lower than the specified significance level, it can be concluded that Capital Structure does not affect Earnings Quality, which means that the Investment Opportunity Set has a significant influence or contribution to changes in Earnings Quality. The research results show that the Capital Structure variable does not have a significant influence on changes in Earnings Quality, in other words, changes in the Investment Opportunity Set and Capital Structure can explain around 3.3 percent of changes or fluctuations in Earnings Quality, and the remaining part.